The Impact of Entrepreneurial Behavior on Sales Volume - Adjeng Tiara Eltari; Hendrati Dwi Mulyaningsih (Research Synergy Foundation, 2017)
This research was conducted at the Culinary Hawkers that located on Highway Sukapura, Dayeuhkolot, Bandung. This study examines the Entrepreneurial behaviour which resulted in increased sales volumes. Almost all Culinary Hawkers on Highway Sukapura doesn’t yet have the entrepreneurial behavior in accordance with the characteristics - traits mentioned by Suryana, Confident, Own initiative, Have achievement motive, Having leadership, and Dare to take risks with the full calculation. The purpose of this study was to investigate the influence of entrepreneurial behavior to the merchant's sales volume culinary pavement on Highway Sukapura, Dayeuhkolot, Bandung.Researchers used quantitative research methods. The population in this study was 63 Merchants Culinary Street on Highway Sukapura. Samples are 63 street vendors in JalanSukapura. Data were analyzed using simple regression analysis.The results showed that entrepreneurial behavior affect the sales volume of culinary street traders in Highway Sukapura. Based on the calculation coefficient of determination (R2) can be seen the effect of entrepreneurial behavior variables (X) on sales volume (Y) is approximately 94%. While the remaining 6% are influenced by other factors such as competence, performance, and motivation.